Savings from reducing low‐value general surgical interventions. Issue 1 (8th November 2017) - Malik, H. T.; Marti, J.; Darzi, A.; Mossialos, E.
Abstract : Background: Finding opportunities for improving efficiency is important, given the pressure on national health budgets. Identifying and reducing low‐value interventions that deliver little benefit is key. A systematic literature evaluation was done to identify low‐value interventions in general surgery, with further assessment of their cost. Methods: A multiplatform method of identifying low value interventions was undertaken, including a broad literature search, a targeted database search, and opportunistic sampling. The results were then stratified by impact, assessing both frequency and cost. Results: Seventy‐one low‐value general surgical procedures were identified, of which five were of high frequency and high cost (highest impact), 22 were of high cost and low frequency, 23 were of low cost and high frequency, and 21 were of low cost and low frequency (lowest impact). Highest impact interventions included inguinal hernia repair in minimally symptomatic patients, inappropriate gastroscopy, interval cholecystectomy, CT to diagnose appendicitis and routine endoscopy in those who had CT‐confirmed diverticulitis. Their estimated cost was €153 383 953. Conclusion: Low‐value services place a burden on health budgets. Stopping only five high‐volume, high‐cost general surgical procedures could save the National Health Service €153 million per annum. Abstract : Considerable savings possible